EFEKTIVITAS PEMBELAJARAN TEMATIK INTEGRATIF BERBASIS MULTIPLE INTELLIGENCE DAN HASIL BELAJAR SISWA PADA TEMA TUMBUHAN DAN HEWAN - Yulia Pramusinta; Chindy Ema Elvianah; Tiara Anggraini Maghfiroh (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The 2013 curriculum is a competency-based curriculum designed to anticipate 21st century competency needs. In this century, as we can witness together, the ability of creativity and communication will be very important. Intelligence in processing a science is an important thing to do, one of which is to sharpen multiple intelligences in students to produce a maximum student achievement, especially in thematic learning. The purpose of this study was to examine the effect of thematic learning and multiple intelligence on student learning outcomes. This research is an experimental quantitative research, this research was conducted on science class 5 subjects on the theme of plants and animals. The subjects in this study were 25 students. When this research was conducted in January-February 2017. The instrument used for data collection was the questionnaire / questionnaire method. Testing the credibility of the instrument using the instrument validity and reliability test. Data collection procedures in this study used observation, questionnaires / questionnaires and documentation. The data analysis technique of this study uses multiple linear regression analysis. The results showed there was a significant influence between integrative thematic learning and multiple intelligence in improving student learning outcomes.